PEMANFAATAN MEDIA TIK SIMULASI SEBAGAI SUBSTITUTE DEMONSTRASI PADA PEMBELAJARAN ALAT UKUR - Liza Fitri; Agus Suyatna; Viyanti Viyanti (Jurnal Pembelajaran Fisika, 2014)
The purposes of this study are: to determine the increasing of students’ cognitive learning outcomes, to grow the students’ Science Process Skills, to grow the character of students, to improve activities of the students, and to grow the attitudes of students on study of measuring instruments with the use of ICT simulation media as a substitute of demonstration. The research had been done in the first semester of 2013/2014 in SMP Negeri 1 Batu Brak, West Lampung. The population was every students of class VII and the sample was class VIIA. The research design is used One-Shot Case Study. The research is concluded that a positive attitudes has been grown on students by using ICT simulation media as a substitute of demonstration on study of measuring instruments, to increase the students’ cognitive learning outcomes, to grow the Science Process Skills of the students, form the character of the students, and to improve the activities of the students.Penelitian ini bertujuan untuk: mengetahui peningkatan hasil belajar ranah kognitif siswa, menumbuhkan Keterampilan Proses Sains siswa, membangun karakter siswa, meningkatkan aktivitas siswa, dan menumbuhkan sikap siswa pada pembelajaran alat ukur dengan memanfaatkan media TIK simulasi sebagai substitute demonstrasi. Penelitian dilaksanakan pada semester ganjil tahun ajaran 2013/2014 di SMP Negeri 1 Batu Brak, Lampung Barat. Populasi dalam penelitian ini adalah seluruh siswa kelas VII dan sampel penelitian adalah kelas VIIA. Desain pada penelitian ini adalah One-Shot Case Study. Hasil penelitian ini yaitu menumbuhkan sikap positif siswa terhadap pelaksanaan pembelajaran alat ukur menggunakan media TIK simulasi sebagai substitute demonstrasi, meningkatkan hasil belajar ranah kognitif siswa, menumbuhkan Keterampilan Proses Sains siswa, membentuk karakter siswa, dan meningkatkan aktivitas siswa.Kata kunci: aktivitas siswa, karakter siswa, keterampilan proses sains, media TIK simulasi, substitute demonstrasi.